Holiday Native Land (2023) de Nicolas Renaud et Brian Virostek: critique d’un appétit impérial insatiable - Dubé, Joëlle (RACAR : Revue d'art canadienne / Canadian Art Review, 2025)
This article focuses on the short-film Holiday Native Land (2023), a collaborative work between Wendat visual artist Nicolas Renaud and Ontarian visual artist Brian Virostek, through the intersection of Indigenous Studies, sociology, and the history of national parks. The split-screen short movie is composed of archival national parks advertisements and reads—through our contemporary eyes—as an eerie testament to the imperialist ambitions of both private economic interests and Canadian government bodies. This article concentrates primarily on the linguistic and visual deployment of this official promotional rhetoric through a close analysis of Holiday Native Land, examining the intimate link that exists between this rhetoric and the emergence of a distinctly Canadian imperialism. Finally, it demonstrates how this same rhetoric is indissociable from an insatiable imperial appetite, one that translates into an unquenchable desire to neutralize the Other by metaphorically consuming them.